Το θεατρικό παιχνίδι στο μάθημα της ιστορίας: Η Μύρτις μάς ταξιδεύει από τον λοιμό των Αθηνών στην πανδημία του σήμερα - Παπαγρηγοράκης, Μ. Ι.; Δημητριάδης, Δ.; Γαλανάκη, Ε.; Γουργιώτου, Ε.; Τόσκας, Ά.; Bin, M.; Σωτηρίου, Σ.; Μικεδάκη, Μ. (Διάλογοι! Θεωρία και Πράξη στις Επιστήμες της Αγωγής και της Εκπαίδευσης, 2021)
This article proposes and describes an educational scenario for 4th, 7th and 10th grade school history. The main goal of this scenario is to help students understand the historical dimension of the phenomenon of the pandemic and to develop critical thinking towards it, in order to enhance their mental resilience. The main historical character of this scenario is Myrtis. The use of drama game techniques is proposed as the main teaching method for the scenario's implementation. The title of the educational scenario is the following: «Travelling with Myrtis from the plague of Ancient Athens to the pandemic of covid-19». In the scenario, students travel to the plague of Ancient Athens through an imaginary journey to the past with Myrtis. After traveling through the pandemics of different historical periods (plague, smallpox, cholera), they arrive at their experience of the pandemic in the present. The design was based on the theories of the educational scenario and theatre pedagogy.